Among-individual variation in white seabream (Diplodus sargus) spatial behaviour and protection in a coastal no-take area - De Benito Abelló, Carmela (2022)
Marine protected areas (MPAs), and specially no-take areas (NTAs), play an important role in protecting target populations from fisheries. When developing spatial conservation and management tools, the design has mainly focused on population-level measures of fish home ranges, spawning and feeding areas, and migration routes. Intraspecific differences in fish behaviour, however, are often not accounted for, even though they could influence the level of realized protection. In this study, we investigated the intraspecific variation in spatial behaviour of a harvested fish, Diplodus sargus, and how it impacts the degree of protection granted by a NTA in the south of Portugal. We identified four behavioural types according to their spatial behaviour: residents, commuters, seasonal visitors, and single users. Time at risk (i.e. outside the NTA) greatly varied among the four groups, but also over the year for the seasonal and the single users. Our study shows how acoustic telemetry can assist spatial conservation and fisheries management and provides novel insight regarding the role of individual variation in behaviour to understand protection granted by MPAs to harvested species. It also suggests that incorporating such information into all stages of MPA design and implementation can result in increased resilience of the protected populations.